PENGOLAHAN BAHAN PUSTAKA DI SMA MUHAMMADIYAH 2 PONTIANAK - Sabrina, Siti Nur; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe library materials arrangement in SMA Muhammadiyah 2 Pontianak is different from another school library. The purpose of this final project is to explain the manual arrangement of library materials in SMA Muhammadiyah 2 Pontianak. The method being used was the descriptive qualitative method, while the collection data methods were observation method, interview method, and study document method. The informants consist of 2 persons, which were the librarian and the head librarian. The result shows that because of the lack of experts on the library materials arrangement process, hence the process can not be done optimally. In the arrangement process, the librarian using book inventorying, stamping, classification based on the inventorying book number, pasting the call number on books, and directlyaligning the books in collection shelves. It means the library materials arrangement that had done was not appropriate withthe which exsts arrangement standard. Keywords: Library materials arrangement, classification, school library